Volatile compounds produced by Calotropis procera (Family: Asclepiadaceae] leaves that aid in the repulsion of grazers - Russell, Dennis (2011)
Calotropis procera, a desert shrub with large succulent leaves, but without protective spines, was investigated for volatile substances that aid in repelling grazing animals. It was found that fresh C.perocieraleaves producedvolatile organic compounds that included thioacetic acid, 2,3-dihydro-3,5-dihydroxy-6-mehtyl-4H-pyran-4-one, and 5-hydroxymethyl-2-furancarboxaldehyde. The most probable repellent of grazers from leaves of C.procera was thioacetic acid. The ecological significance is that C.procera uses irritating volatiles to repel desert grazers in addition to toxins rather than the usual plant defense mechanisms, such as the production of numerous spines.